Colorblindness as Identity: Key Determinants, Relations to Ideology, and Implications for Attitudes about Race and Policy. (October 2017) - Hartmann, Douglas; Croll, Paul R.; Larson, Ryan; Gerteis, Joseph; Manning, Alex
Colorblindness is often conceptualized as a set of deeply held but unrecognized ideological tenets. However, we believe that colorblindness has also now become an explicit cultural discourse involving self-conscious claims and specific convictions. To illustrate this point—which has both conceptual and empirical implications—we introduce the notion of colorblindness as identity. We define this concept as subjectively meaningful, self-asserted identification with colorblindness. We use data from a nationally representative survey to explore the social determinants of colorblind identification and assess its relationship to both colorblind ideologies and standard attitudinal measures. We find that a relatively large percentage of Americans across racial lines identify as colorblind. Furthermore, such identification is connected to racial ideologies but not all tenets of colorblind racism. For white Americans, colorblind identification is associated with decreased perceptions of social distance, but not support for policies designed to ameliorate the effects of racial discrimination. We conclude that colorblind identification is a unique social phenomenon, connected to views on race but not always in the ways that existing research would predict. We also suggest directions for further exploration of the depth of colorblindness as an identity form and implications for theorizing colorblind discourse more generally.